Predictors of 1-year mortality in patients with aortic regurgitation after transcatheter aortic valve implantation: an analysis from the multicentre German TAVI registry. Issue 16 (3rd June 2014) - Abdel-Wahab, Mohamed; Zahn, Ralf; Gerckens, Ulrich; Linke, Axel; Sievert, Horst; Schäfer, Ulrich; Kahlert, Philipp; Hambrecht, Rainer; Sack, Stefan; Hoffmann, Ellen; Senges, Jochen; Schneider, Steffen; et al.
Abstract : Objective: Residual aortic regurgitation (AR) after transcatheter aortic valve implantation (TAVI) has been associated with increased mortality. Nevertheless, a considerable proportion of these patients survives and appears to tolerate AR. Identification of patients at higher risk of death may assist in tailoring therapy, but predictors of mortality in this subset of patients is largely unknown. Methods: A total of 1432 patients were included in the German TAVI registry. One-year follow-up data were available for 1318 patients (92%). Of the latter, 201 patients (15.2%) had more-than-mild AR as evaluated by angiography and represent the population of the current analysis. Among these patients, baseline demographic, clinical, echocardiographic and angiographic characteristics were compared among survivors and non-survivors to identify factors associated with mortality at 1 year. Results: Mean age was 81.2±6.6 years and men represented 55%. The mean logistic EuroSCORE was 22±15%. Overall, 92% of patients received the Medtronic CoreValve and 8% received the Edwards Sapien valve. At 1 year, 61 patients (31%) with more-than-mild post-TAVI AR had died. Compared with patients who survived, patients who died had more commonly coronary artery disease, peripheral arterial disease and chronic renal impairment. Patients who died had a lower baseline LVEF (44±18% vs 52±16%, p=0.002), higher prevalence of more-than-mild (≥2+) mitral regurgitation (44% vs 27%, p=0.001), and a higher systolic pulmonary artery pressure (51±18 mm Hg vs 44±19 mm Hg, p=0.002), but the severity of aortic stenosis was similar, and the prevalence and severity of pre-TAVI AR was comparable (any AR in 88% vs 83%, respectively, p=0.29). Using Cox regression analysis, only baseline mitral regurgitation ≥2+ (HR 1.77, 95% CI 1.05 to 2.99, p=0.03) and systolic pulmonary artery pressure (HR 1.15, 95% CI 1.01 to 1.33, p=0.04) were independently associated with 1-year mortality, while female gender was protective (HR 0.54, 95% CI 0.30 to 0.96, p=0.03). Conclusions: We identified preprocedural characteristics associated with 1-year mortality in patients with more-than-mild AR after TAVI. More-than-mild baseline mitral regurgitation, higher systolic pulmonary artery pressure and male gender were independently associated with worse outcome.